The English Landscape Garden as an Influence on East Bohemian Parks - Veselovská, Petra (Univerzita Pardubice, 2011)
This bachelor paper deals with the phenomenon of the English landscape park and its influence on Continental architects. First, it is described the development of the landscape park together with the socio-cultural background. On the example of three East Bohemian parks (Heřmanův Městec, Choltice, and Slatiňany) there are analyzed four characteristic features of the landscape park ? water, a path system, plants, and prospects with vistas. It is compared how and to what extent the East Bohemian parks are similar to English ones.
Odraz anglického krajinářství v Čechách na příkladu vybraných východočeských parků
Keywords: britská kultura; 18. století; anglický krajinářský park; východočeské parky; british culture; 18th century; the English landscape garden; the East Bohemian parks